Integrated system for recommending fertilization rates in pineapple (Ananas comosus (L.) Merr.) crop (2017)
In recent years much attention has focused on the impacts of agriculture on climate change, due to this stage specialists in plant nutrition and soil fertility have achieved the task of generating adequate fertilization doses for pineapple to reduce effects on environment. A methodology for Integrated System for Recommending Fertilizer Dose (ISRFD) was used. As a result, seven Thiessen polygons of the average annual rainfall, where rainfall ranged from 1640 to 2841 mm was correlated. Therefore, three major soil groups were defined and classified as subunit level. Likewise, eight doses of fertilizers were generated as follows: N, P2O5 and K2O, with a fertilizer dose, a map is generated according to the cultivar: 230-138-300 for Creole pineapple in Acrisol Cutanic (Chromic, Ferric); 460-161-480 for Cayenne and MD2 in Acrisol Cutanic (Endoclayic, Ferric); 345-161-450 for Cayenne and MD2, 253-138-450 for Creole in Acrisol Cutanic (Endoclayic, Hyperdystric, Ferric); 391-161-450 for Cayenne and MD2 in Acrisol Umbric Cutanic (Endoclayic, Hyperdystric) and Acrisol Umbric Cutanic (Endoclayic, Hyperdystric, Ferric); 207-138-300 for Creole in Acrisol Umbric Cutanic (Endoclayic, Hyperdystric); 253-138-300 for Creole in Acrisol Umbric Cutanic (Endoclayic,Hyperdystric, Ferric); 253-138-360 for Creole in Acrisol Umbric Gleyic (Hyperdystric, Ferric); and 391-161-360 in Cambisol Endogleyic (Clayic, Eutric). These fertilizer doses were supplemented with micronutrients to obtain the expected results.